Insect cold tolerance and repair of chill-injury at fluctuating thermal regimes: role of 70 kDa heat shock protein expression - Tollarová-Borovanská, Michaela; Lalouette, Lisa; Kostál, Vladimír (Cryo letters, 2009)
Expression of heat shock proteins has been proposed as an underlying mechanism of increased cold tolerance in insects exposed to fluctuating thermal regimes (FTRs) in comparison to constant low temperatures (CLTs). We found that the levels of Pahsp70 mRNA increase by up to 3 orders in the linden bugs, Pyrrhocoris apterus exposed to FTR -5 degree C (22h) and 25 degree C (2h). The 2h-long warm pulses, however, were not sufficient for accumulation of PaHSP70 protein and thus no significant difference in expression of PaHSP70 protein was detected between FTR and CLT regimes. Hence, we conclude that the accumulation of PaHSP70 protein is not the mechanism underlying the increased cold tolerance in P. apterus at the particular FTR used in this study. The relevance of some other possible mechanisms is discussed.
Keywords: Insecta; fyziologická adaptace; nízká teplota; RNA, Messenger; Animals; hmyz; mužské pohlaví; messenger RNA; Male; HSP70 Heat-Shock Proteins; zvířata; termoregulace; Body Temperature Regulation; Cold Temperature; proteiny tepelného šoku HSP70; Adaptation, Physiological